Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x^2-2x+3\right)\left(\frac{1}{2x}-5\right)\)
\(=\frac{x^2}{2x}-5x^2-\frac{2x}{2x}+10x+\frac{3}{2x}-15\)
\(=\frac{x^2}{2x}-5x^2-16+10x+\frac{3}{2x}\)
\(=-5x^2+\frac{x^2}{2x}+\frac{20x^2}{2x}+\frac{3}{2x}-16\)
\(=-5x^2+\frac{x^2+20x+3}{2x}-16\)
học tốt
(x^2-2x+3)(1/2x-5)=1/2x^3-5x^2-x^2+10x+3/2x-15=1/2x^3-6x^2+11,5x-15
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (2x2 - x) + 4x - 2 = 0
x(2x - 1) + 2(2x - 1) = 0
(2x - 1)(x + 2) = 0
2x - 1 = 0 hoặc x + 2 = 0
* 2x - 1 = 0
2x = 1
x = \(\frac{1}{2}\)
* x + 2 = 0
x = -2
Vậy x = -2; x = \(\frac{1}{2}\)
b) x2 - 6x + 8 = 0
x2 - 2x - 4x + 8 = 0
(x2 - 2x) + (-4x + 8) = 0
x(x - 2) - 4(x - 2) = 0
(x - 2)(x - 4) = 0
x - 2 = 0 hoặc x - 4 = 0
* x - 2 = 0
x = 2
* x - 4 = 0
x = 4
Vậy x = 2; x = 4
c) x4 - 8x2 - 9 = 0
x4 + x2 - 9x2 - 9 = 0
(x4 - 9x2) + (x2 - 9) = 0
x2(x2 - 9) + (x2 - 9) = 0
(x2 - 9)(x2 + 1) = 0
x2 - 9 = 0 (vì x2 + 1 > 0 với mọi x)
x2 = 9
x = 3 hoặc x = -3
Vậy x = 3; x = -3
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{x}{a}=\dfrac{m-\dfrac{x}{2}}{m}\)
\(\Rightarrow xm=a\left(m-\dfrac{x}{2}\right)\)
\(\Rightarrow xm=am-\dfrac{ax}{2}\)
\(\Rightarrow2xm=2am-ax\)
\(\Rightarrow2xm+ax=2am\)
\(\Rightarrow x\left(2m+a\right)=2am\)
\(\Rightarrow x=\dfrac{2am}{a+2m}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
A. \(256:2^5\cdot4\)
\(=2^6:2^5\cdot2^2\)
\(=2^{6-5+2}\)
\(=2^3\)
B. \(\left(4x^2\right)^8:\left(4x^2\right)^4:\left(4x^2\right)^2\)
\(=\left(4x^2\right)^{8-4-2}\)
\(=\left(4x^2\right)^2\)
\(=\left[\left(2x\right)^2\right]^2\)
\(=\left(2x\right)^4\)
C. \(y^{50}:\left(y^5\right)^3:\left(y^2\right)^{10}\)
\(=y^{50}:y^{15}:y^{20}\)
\(=y^{50-15-20}\)
\(=y^{15}\)